Performance Analysis of Earthquake-Resistant Building Structures with Conventional Columns and Flat Columns - Pangestu, Andika Dwi; amalia, amalia; Edistria, Ega Edistria (Applied Research on Civil Engineering and Environment (ARCEE), 2024)
The structural integrity of a building depends on the ability of its column components to support the loads above them. The strength of a column is greatly influenced by its shape and dimensions. This study aims to analyze the performance of earthquake-resistant building structures with conventional columns and flat columns. This research was conducted by modeling two variations of an 8-story building structure using ETABS software, which are Model 1 with conventional columns and Model 2 with a combination of conventional columns and flat columns using L-shaped and T-shaped columns. The analysis of earthquake loads was performed by using the response spectrum analysis method, while the structural performance and the collapse mechanism of the building were performed by using the pushover analysis method. The results showed that Model 1 had smaller values of internal force, base shear, displacement, and inter-storey drift than Model 2. The results of the structural performance level in both models had the same level, which is Damage Control (DC). The structural collapse mechanism in Model 1 has qualified the requirement of strong column weak beam, while Model 2 has not met this requirement and falls into the column sway mechanism because the first collapse happened in columns. Based on the statistics analysis, there is no significant difference between Model 1 and Model 2, but in terms of maintaining the room area and aesthetic interior, Model 2 with flat columns has more value.